Epidemic Causing the Delay and Strategies for Malaysian Construction Projects - Halimin, Zarith; Mohd Roshdi, Farrah Rina (Research in Management of Technology and Business, 2024)
The epidemic had a significant impact on the construction sector. The construction industry in Malaysia is currently dealing with several issues due to epidemic. The purpose of this study is to identify the causes of these issues and consider potential solutions. This quantitative study utilized survey questionnaire as its research instrument. 159 questionnaires were distributed among G7 contractors in Klang Valley. SPSS version 26 software was used to analyse the data that had been gathered. It was found that project delays, lower revenue, increased spending on safety precautions, issues with the supply chains, and labour shortages are some of the issues faced by construction companies in Malaysia. However, supply chains,a labour shortages, and financial issues were found to be the major challenges faced by the construction sector and have contributed significantly to the delays in construction projects. The findings of the study managed to explain issues faced by construction projects in Malaysia  during the pandemic. These findings can be used to generate sound recommendations and strategies for reducing delays and strengthening the construction sector. Overall, this study contributes to the understanding of epidemic impacts on the construction sector and proposes some strategies to overcome the issues and  to enhance project outcomes